1977
DOI: 10.1007/bf01868149
|View full text |Cite
|
Sign up to set email alerts
|

Internal and external application of photodynamic sensitizers on squid giant axons

Abstract: Squid giant axons were photosensitized by dyes applied internally or externally in air saturated solutions and photochemically modified by visible light. For most dyes the modifications included an irreversible block of sodium channels, a destruction of inactivation in some of the unblocked channels, and a slowing of inactivation. Internal application was up to 100-fold more effective in blocking sodium channels than external application, suggesting a site of block nearer the internal surface. Rose Bengal sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

1981
1981
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 34 publications
2
27
1
Order By: Relevance
“…The latter seemed ineffective when the sodium currents were prevented a second phase of inward current (Bostock 1982). Similarly, photosensitive effects on voltage dependent sodium channels have been reported for many other dyes such as bengale rose, eosin Y in squid axons and lobster neurons (Pooler 1972;Oxford et al 1977;Pooler and Valenzeno 1979). In the present study, a delay of the inactivation of voltage activated inward currents was corroborating these findings.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The latter seemed ineffective when the sodium currents were prevented a second phase of inward current (Bostock 1982). Similarly, photosensitive effects on voltage dependent sodium channels have been reported for many other dyes such as bengale rose, eosin Y in squid axons and lobster neurons (Pooler 1972;Oxford et al 1977;Pooler and Valenzeno 1979). In the present study, a delay of the inactivation of voltage activated inward currents was corroborating these findings.…”
Section: Discussionsupporting
confidence: 81%
“…In the present study, a delay of the inactivation of voltage activated inward currents was corroborating these findings. A previous study showed that the prolongation of channel openings by MB was even more effective when applied intracellularly suggesting a site of action that is closer to the intracellular opening of the channel pore (Oxford et al 1977). This corresponds nicely to the assumed intracellular location of the inactivation gate of the voltage dependent sodium channel (see Hille 1992).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition it was recently shown (20) that the fast inactivation of cloned mammalian A-type K+ channels including Kv1.4 and Kv3.4 expressed in Xenopus oocyte is abolished by oxidation and maintained by reducing agents like glutathione. Finally, photomodifications of squid axons produce a prolongation of action potentials due to a modification of K+ and Na+ currents (44) and H202 has been shown to inhibit the fast inactivation of Kv3.3 and Kv3.4 K+ channels (45).…”
Section: Resultsmentioning
confidence: 99%
“…If a successful recording is not achieved on the first attempt, repeat with fresh electrodes until a recording is obtained or the tissue is disrupted to the point at which the axon is no longer visible. However, it is also important to quickly place the electrode next to the axon to minimize the amount of fluorescent exposure, which can cause phototoxicity, bleaching and may affect physiological properties of the cell [29][30][31] . Once a segment of axon is successfully suctioned into the recording electrode, recordings can be obtained for several hours.…”
Section: Discussionmentioning
confidence: 99%